140k views
5 votes
Solve for r.

√2/3r + 1 = 23

Solve for r. √2/3r + 1 = 23-example-1
User Symbolic
by
4.7k points

2 Answers

5 votes

Answer:

B) r=33*sqrt(2)

Explanation:

sqrt(2)/3r+1=23

sqrt(2)/3r=23-1

sqrt(2)/3r=22

sqrt(2)r=22*3

sqrt(2)r=66

r=66/sqrt(2)

r=66*sqrt(2)/(sqrt(2)*sqrt(2))

r=(66*sqrt(2)/2

r=33*sqrt(2)

User Turbojohan
by
4.5k points
5 votes

Answer:

2nd option

Explanation:


(√(2) )/(3) r + 1 = 23 ( subtract 1 from both sides )


(√(2) )/(3) r = 22 ( multiply both sides by 3 to clear the fraction )


√(2) r = 66 ( divide both sides by
√(2) )

r =
(66)/(√(2) ) ×
(√(2) )/(√(2) ) ( rationalising the denominator )

r =
(66√(2) )/(2) = 33
√(2)

User Jayanta
by
5.4k points